Atrial Transcriptional Profiles of Molecular Targets Mediating Electrophysiological Function in Aging and Pgc-1β Deficient Murine Hearts - Edling, Charlotte E.; Fazmin, Ibrahim T.; Chadda, Karan R.; Ahmad, Shiraz; Valli, Haseeb; Huang, Christopher L.-H.; Jeevaratnam, Kamalan (Frontiers in Physiology, 2019)
Background Deficiencies in the transcriptional co-activator, peroxisome proliferative activated receptor, gamma, coactivator-1β are implicated in deficient mitochondrial function. The latter accompanies clinical conditions including aging, physical inactivity, obesity, and diabetes. Recent electrophysiological studies reported that Pgc-1β-/- mice recapitulate clinical age-dependent atrial pro-arrhythmic phenotypes. They implicated impaired chronotropic responses to adrenergic challenge, compromised action potential (AP) generation and conduction despite normal AP recovery timecourses and background resting potentials, altered intracellular Ca2+ homeostasis, and fibrotic change in the observed arrhythmogenicity. Objective We explored the extent to which these age-dependent physiological changes correlated with alterations in gene transcription in murine Pgc-1β-/- atria. Methods and Results RNA isolated from murine atrial tissue samples from young (12–16 weeks) and aged (>52 weeks of age), wild type (WT) and Pgc-1β-/- mice were studied by pre-probed quantitative PCR array cards. We examined genes encoding sixty ion channels and other strategic atrial electrophysiological proteins. Pgc-1β-/- genotype independently reduced gene transcription underlying Na+-K+-ATPase, sarcoplasmic reticular Ca2+-ATPase, background K+ channel and cholinergic receptor function. Age independently decreased Na+-K+-ATPase and fibrotic markers. Both factors interacted to alter Hcn4 channel activity underlying atrial automaticity. However, neither factor, whether independently or interactively, affected transcription of cardiac Na+, voltage-dependent K+ channels, surface or intracellular Ca2+ channels. Nor were gap junction channels, β-adrenergic receptors or transforming growth factor-β affected. Conclusion These findings limit the possible roles of gene transcriptional changes in previously reported age-dependent pro-arrhythmic electrophysiologial changes observed in Pgc-1β-/- atria to an altered Ca2+-ATPase (Atp2a2) expression. This directly parallels previously reported arrhythmic mechanism associated with p21-activated kinase type 1 deficiency. This could add to contributions from the direct physiological outcomes of mitochondrial dysfunction, whether through reactive oxygen species (ROS) production or altered Ca2+ homeostasis.